ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL FUNGSI KOMPOSISI DITINJAU DARI PERBEDAAN GENDER - Eric Dwi Putra; Zidna Rizqoh (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
This study was conducted with the aim of identifying errors that occur when students solve composition function problems by paying attention to gender differences. The research subjects were four students of class XI, two male students and two female students. The research method used was descriptive qualitative. Tests and interviews were conducted to collect data. The data were then analyzed by examining the students' answer sheets and classifying the errors made into four types, namely concept, principle, fact, and operation errors. The findings showed that male students made more errors than female students, especially in the category of fact and operation errors. Fact errors made by male students are errors in writing arithmetic operation signs, this is because male students do not understand the concept of multiplication and addition operation signs. While the error in determining the final answer was caused by an error in the previous process, where male students could not do the calculation correctly so that they got the wrong final result. The conclusion of this study confirms that female students have an advantage in the ability to solve math problems compared to male students.